The life and death of good intentions? Unravelling participatory design processes of three Dutch solar power plants - Enserink, Merel; Van Etteger, Rudi; Stremke, Sven (Energy research & social science, 2024)
Public participation in renewable energy projects is required in The Netherlands, as it is key to a socially just energy transition which embraces local and societal concerns. Participatory design processes can address the call for public participation and achieve qualitative aims stated in policy guidelines. However, todays permit procedures of local authorities focus on technical and economic factors, while other societal concerns seem to disappear in the development process of solar power plants (SPPs). In this study, we unravel the participatory design processes of three Dutch cases to explore their benefits and limitations, and implications for future policies. We find that local inhabitants have a strong position in these processes. Moreover, we find an imbalance of proposed measures materializing in the final design. Although there is attention for societal concerns beyond those of the local inhabitants, measures that address societal concerns are more frequently altered or removed. This is mainly due to economic factors and a conventional approach to SPP development as monofunctional land-use. Based on our research, we argue for redressing the balance between the concerns of local inhabitants, such as nuisance, and broader societal concerns, such as biodiversity and landscape quality. We recommend improving policy, or directly changing subsidy requirements, to ensure a better balance of involved stakeholder groups and their possibilities to participate and affect the decision-making in SPP design processes. This would foster trajectories towards more environmental sustainable and socially just deployment of renewable energy technologies for the energy transition. •Dutch policies on participation and societal concerns in SPP development are absent or unclear.•First study analysing benefits & limitations of participatory design processes in Dutch SPP development.•Participatory design benefits local inhabitants and experts, contributing to procedural justice.•Individual priorities at the project level do not align with broader societal concerns.•Policies need to ensure a better balance of stakeholders participating and their abilities to affect decisions.